2003
DOI: 10.1093/gerona/58.2.m171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strength and Power Training on Physical Function in Community-Dwelling Older Adults

Abstract: Power training was more effective than strength training for improving physical function in community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
237
7
27

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(298 citation statements)
references
References 24 publications
22
237
7
27
Order By: Relevance
“…The inclusion of explosive contractions in strength training results in overall neuromuscular adaptations in the elderly, such as increases in the maximal concentric power, the rates of force development and rapid muscle activation, and maximal dynamic strength (Häkkinen et al 2001;Izquierdo et al 2001a). Moreover, certain studies have reported that strength training using high velocity during concentric contractions results in greater improvements in functional capacity when compared with strength training using only slow velocity of contractions (Earles et al 2001;Sayers et al 2003;Henwood et al 2008;Miszko et al 2003;Orr et al 2006;Bottaro et al 2007;Correa et al 2012;Pereira et al 2012;Reid and Fielding 2012). In the study by Pereira et al (2012), 12 weeks of high-speed power training improved walking speed and performance on functional tests, such as "sit to stand" and "get up and go" in elderly women.…”
Section: Long-term Concurrent Training Programsmentioning
confidence: 99%
“…The inclusion of explosive contractions in strength training results in overall neuromuscular adaptations in the elderly, such as increases in the maximal concentric power, the rates of force development and rapid muscle activation, and maximal dynamic strength (Häkkinen et al 2001;Izquierdo et al 2001a). Moreover, certain studies have reported that strength training using high velocity during concentric contractions results in greater improvements in functional capacity when compared with strength training using only slow velocity of contractions (Earles et al 2001;Sayers et al 2003;Henwood et al 2008;Miszko et al 2003;Orr et al 2006;Bottaro et al 2007;Correa et al 2012;Pereira et al 2012;Reid and Fielding 2012). In the study by Pereira et al (2012), 12 weeks of high-speed power training improved walking speed and performance on functional tests, such as "sit to stand" and "get up and go" in elderly women.…”
Section: Long-term Concurrent Training Programsmentioning
confidence: 99%
“…Interventions based on physical activity programs, including resistance exercise, have been shown to improve a variety of performance measures, such as walking speed, speed in climbing a flight of stairs, balance, and to rise up from a sitting position [32,33]. Other intervention studies with short follow-up suggest that physical activity can increase the score of SPPB [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…No indivíduo idoso está claro que a potência e não a força muscular é o fator determinante para a melhora da independência e da qualidade de vida (44,45) , além de ser melhor indicador para a prevenção do risco de quedas (46) . Assim, no idoso, é necessário que o fortalecimento muscular seja feito em alta intensidade.…”
Section: Benefícios Da Atividade Física Para a População Idosaunclassified